Influence of shade, curing mode, and aging on the color stability of resin cements - Janes Francio Pissaia; Gisele Maria Correr; Carla Castiglia Gonzaga; Leonardo Fernandes Cunha (Universidade Estadual de Campinas, 2016)
The color stability of resin cements is essential for aesthetic restorations. Aim: To evaluate the influence of shade and aging time on the color stability of two light-cured and two dual-cured resin cements. Methods: The CIE-Lab color parameters (n=6) were measured immediately after sample preparation and at 7, 30 and 90 days of aging in distilled water. The color difference (∆E) was calculated and then analyzed by three-way ANOVA for repeated measures and Tukey's HSD test (α=0.05). Results: ∆E was higher for transparent resin colors, followed by dark and light colors. The mean values of ∆E were lower for both light-cured resin cements compared to the dual-cured cements. As the aging time increased, ∆E values increased. Conclusions: The light-cured resin cements showed greater color stability. The lighter shades of luting were more likely to display a greater color change.